Rhizosphere Microenvironments of Eight Common Deciduous Fruit Trees Were Shaped by Microbes in Northern China - Si, Peng; Shao, Wei; Yu, Huili; Yang, Xiaojing; Gao, Dengtao; Qiao, Xiansheng; Wang, Zhiqiang; Wu, Guoliang (Frontiers in Microbiology, 2018)
Fruit tree species have significant impacts on the physicochemical properties of soil, the soil enzyme activity and the soil microbial community. Analyzing the physicochemical properties, enzyme activity and microbial community of the rhizosphere soil among different species of deciduous fruit trees in northern China is significantly beneficial in clarifying the differences in the rhizosphere environment among different species of fruit trees; this analysis can facilitate the development of specialized fruit tree fertilizers tailored to these characteristics to meet the fruit trees’ demand for nutrients, increasing fruit production and achieving sustainable agricultural development. In this study, we examined the soil physicochemical properties, enzyme activity, CLPP (community level physiological profile) and microbial structure diversity based on tree species. The results showed that the content of soil available minerals, the pH, the soil enzyme activity, the microbial community utilization of six types of carbon substrates and the microbial structure diversity in the rhizosphere were significantly different among the deciduous fruit trees. An RDA (redundancy analysis) showed that the soil pH, ammonia nitrogen content and invertase activity were closely related to the soil microbial community. The Pearson correlation coefficients between the bacterial and fungal genus relative abundances and environmental factors revealed that the soil microbial utilization of the six carbon sources, nitrate nitrogen content, and invertase activity were negatively correlated with Ambiguous and Alternaria; however, they were positively correlated with pH. The ammonia nitrogen content was positively correlated with carbon source utilization and negatively correlated with Ambiguous, Lysobacter, Nitrospira, Alternaria, Fusarium and Colletotrichum. Invertase was positively correlated with carbohydrates, carboxylic acids, amino acids, amines and organic matter content. Interestingly, it was closely related to the fungal community; positively correlated with Mortierella, Geomyces, Lysobacter, and Chaetomium; and negatively correlated with Alternaria, Fusarium and Colletotrichum. In addition, Ambiguous had the most significantly negative correlation with microbial carbon utilization. Hence, the soil physicochemical properties, enzyme activity and microbial community were significantly affected by tree species. Additionally, a variety of environmental factors was closely related to the microbial community in the rhizosphere soil of eight species of deciduous fruit trees.